Comparative Efficacy of Controlled Physiotherapy Exercises Versus Traditional Midwife Massage in Lactating Working Women with Neck Pain: A Randomized Controlled Study - Negi, Nidhi; khan, Jafar; Annamalai, KM.; Goyal, Smita Barya; Jain, Vardhman; Rai, Richa Hirendra; Pal, Renuka; R Qureshi, Abid; Jain, Preksha; Kania, Vaishnavi (Journal of Neonatal Surgery, 2025)
Background: Neck pain is a common musculoskeletal complaint in postpartum women, particularly those resuming desk-based employment during lactation. This study aimed to compare the effectiveness of controlled physiotherapy exercises with traditional massage by midwives in alleviating neck pain in lactating females with desk job profiles. Methods: A 12-week randomized controlled study was conducted on 30 lactating women aged 18–40 years experiencing neck pain. Participants were allocated equally into two groups (n=15 each): Group A received traditional massage therapy by midwives, while Group B underwent a structured physiotherapy exercise regimen. The Neck Disability Index (NDI) and Shoulder Pain and Disability Index (SPADI) were administered at baseline and at 15-day intervals. Statistical analysis was performed using independent t- tests. Results: Both groups demonstrated improvement; however, Group B showed significantly greater reductions in NDI and SPADI scores at Day 61–75 and Day 76–90 (p<0.001). Group B’s SPADI scores decreased from 105.53 to 22.87, while NDI scores declined from 44.93 to 4.07. Conclusion: Controlled physiotherapy exercises proved significantly more effective than traditional midwife massage in reducing neck and shoulder pain and disability in lactating working women. This highlights the necessity of incorporating targeted physiotherapy into postpartum care for women with sedentary occupational demands.